ROLE OF THE IMMUNE SYSTEM IN THE BIOLOGY OF AUTISM SPECTRUM DISORDERS - BHUVANESH SUKHLAL KALAL,; SHAM S BHAT,; VINITHA RAMANATH PAI,; VEENA KM,; ANIL KAKUNJE, (International Journal of Pharma and Bio Sciences, 2016)
Discovery of autoantibodies that target brain proteins in autistic children and their mothers is an interesting finding. The circulating maternal autoantibodies directed towards fetal brain proteins are highly specific for autism. Furthermore, cellular immune system in autistic children suggests that there may be a defect in signaling pathways that are shared by the immune and central nervous systems. Exploration of the role of immune system in neural development is of great interest in recent research, which may have profound implications for diagnosis and treatment of autism. This review is focused on the most recent research concerning the potential role of immune system dysfunction in autism.